2021
DOI: 10.3389/fphys.2021.758299
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intensity on Changes in Cardiac Autonomic Control of Heart Rate and Arterial Stiffness After Equated Continuous Running Training Programs

Abstract: Background: It is well known that exercise training has positive effects on both cardiac autonomic function and arterial stiffness (AS). However, it is not clear that which exercise training variables, intensity or volume, or both, play a crucial role in this regard. This study investigates the chronic effects of high-volume moderate-intensity training (HVMIT) and low-volume high-intensity training (LVHIT) on heart rate variability (HRV) and AS in sedentary adult men.Materials and Methods: Notably, 45 males (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(37 citation statements)
references
References 53 publications
(69 reference statements)
1
35
0
1
Order By: Relevance
“…The authors concluded that constant aerobic exercise was not enough stimulus to unveil cardiac functional gains in the interceded sample. Likewise, other reports denoted that 12 weeks of intervention induces HR reduction in age-matched subjects, such as in our sample [ 41 , 47 ]. Thus, a more-prolonged, unsupervised program could have helped to denote a major significance in HR reduction.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The authors concluded that constant aerobic exercise was not enough stimulus to unveil cardiac functional gains in the interceded sample. Likewise, other reports denoted that 12 weeks of intervention induces HR reduction in age-matched subjects, such as in our sample [ 41 , 47 ]. Thus, a more-prolonged, unsupervised program could have helped to denote a major significance in HR reduction.…”
Section: Discussionsupporting
confidence: 77%
“…Nevertheless, the RMSSD and HF were not modified in either HIIT intervention. Unlike the other reports, our study utilized 14 and 21 min of total volume per session, a minor time employed in comparison to other authors who applied larger volume durations in their programs (~25–60 min) [ 41 , 52 ]. The null effects of HIIT-14 on HRV variables were compatible with the experiments conducted by Soltani et al, where the researchers determined that HRV adaptations are intensity- and volume-dependent [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, electronic database searches retrieved a total of 9201 references after deleting duplicates. Sixty-seven studies were selected after reviewing titles and abstracts, of which, 26 were included in the qualitative synthesis after reviewing the full-text [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ] and 41 were excluded as follows: (a) participants ( n = 12); (b) interventions ( n = 11); (c) comparison ( n = 7); (d) outcomes ( n = 7); (e) data previously published ( n = 2) and (f) language ( n = 2). Out of all the studies included in the qualitative synthesis, seven were excluded from the quantitative synthesis due to insufficient information to calculate the ES ( n = 5) [ 65 , 71 , 75 , 76 , 86 ] or the findings reported were not pooled ( n = 2) [ 72 , 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…Included studies were published from 1995 to 2022. Out of all the 26 studies included [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ], 20 (77%) were randomised [ 66 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ] and six (23%) were non-randomised [ 65 , 67 , 77 , 78 , 79 , 80 ]. Eleven studies (42%) recruited exclusively male participants [ 67 , 70 , 71 , 74 ,…”
Section: Resultsmentioning
confidence: 99%